Development of a device that assists in the recovery of the flexion-extension movement of the wrist (2017)
"The development of devices that assist in the rehabilitation of motor skills play an important role in patients with acquired neurological damage, since this diagnosis affects in 86% the human motion. This document summarizes the design process for a device that assists in the rehabilitation of the flexion-extension movement of the wrist, the manufacturing process of a prototype, and the system-wide functional tests. The starting point of this project is the analysis of the dynamic behavior of the wrist, its limitations and requirements. In addition, the definition and development of a therapy that follows the techniques of the Kabat?s method. The design process is focused on the selection of the best set of structure, actuation system and control system to obtain a portable, space-restricted, ergonomic, stable and safe device. It consists mainly, of a mechanism that is capable of giving the range of maximum amplitude in flexion and extension".-- Tomado del Formato de Documento de Grado.